1999
DOI: 10.1093/ps/78.10.1377
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resistance to Pasteurella multocida among turkey lines

Abstract: Previous research has shown that a line (F) of turkeys selected long-term for increased 16-wk body weight was more susceptible to challenge with washed Pasteurella multocida than a randombred control line (RBC2), the base population of F. A previous study also indicated that the mortality of the F line following challenge with P. multocida was similar to that of sire lines from two of the three major primary breeders. The purpose of the present study was to compare the resistance of the sire line from the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The developmental pattern obtained by the PCA methodology can aid in the planning of more efficient experimental designs so the developmental stage of individuals can be more accurately assessed. the last 30 yr comparing the RBC2 and F line turkeys for various aspects of growth, reproductive fitness, and disease resistance (Nestor et al, 1999a;Nestor et al, 1999b). The F-line turkeys weigh approximately twice as much as the RBC2 at selection age (16 wk), but there are no correlated increases in the proportional weight of the breast muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental pattern obtained by the PCA methodology can aid in the planning of more efficient experimental designs so the developmental stage of individuals can be more accurately assessed. the last 30 yr comparing the RBC2 and F line turkeys for various aspects of growth, reproductive fitness, and disease resistance (Nestor et al, 1999a;Nestor et al, 1999b). The F-line turkeys weigh approximately twice as much as the RBC2 at selection age (16 wk), but there are no correlated increases in the proportional weight of the breast muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Observations in chickens and turkeys have revealed the host immune response has been negatively effected by selection for larger, heavier bodied, faster growing birds with highly improved feed efficiencies (Quereshi & Havenstein, 1994;Nestor et al ., 1999;Li et al ., 1999a,b). The traits of the modern commercial chicken and turkey allow producers to harvest larger, market-ready birds in less time than could be done previously.…”
Section: Introductionmentioning
confidence: 99%
“…These differences included decreased non-specific phagocytic capabilities, as well as increased populations of CD4 ' /CD8 ( T cells, and an increase in mortality from bacterial infections as compared with random-bred turkeys from the same lines (Li et al ., 1999a(Li et al ., ,b, 2000a(Li et al ., ,b, 2001). Nestor and others have shown through the use of lines of turkeys selected for higher body weights that these turkeys have reduced disease resistance and are more susceptible to infections with Pasteurella and Newcastle disease virus (Tsai et al ., 1992;Nestor et al ., 1999). These studies indicated that the acquired immune response was in large part unaffected by selection for large-bodied turkeys, although some differences were noted (Sacco et al ., 1994;Li et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%